Efficacy of Philippine granulated coal ash (GCA) for the improvement of water quality at Estero de San Miguel - Fainsan, Peter Paul C.; Galope, Christian S.; Resurreccion, Augustus C. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
The water quality of Estero de San Miguel has been constantly failing standards, as untreated wastewater from nearby establishments drain into this tributary of the Pasig river. The accumulation of organic matter in the stream maintain the eutrophic and hypoxic environment detrimental to the benthic ecosystem. Over the years, studies have shown the ability of granulated coal ash (GCA) to adsorb certain nutrients that degrade water quality. In Japan, GCA has been widely implemented for the improvement of the sediment and water quality in littoral regions, as it effectively decreases harmful components at a low cost since fly ash, a component of GCA, is a waste product of coal-fired plants. With this, a locally produced Philippine GCA was produced and characterized. Consequently, a GCA installation was erected at the Estero de San Miguel. The objective of this study is to determine the efficacy of the Philippine GCA in wastewater remediation using a batch experiment of the samples from the Estero de San Miguel, while also monitoring the GCA installation. This will be compared to Japan GCA in terms of effectiveness, while considering water quality standards. The batch experiment is comprised of fourteen setups with three different ratios of volumes of wastewater to GCA placed in jars and observed over a period of 28 days. Water quality parameters such as pH, dissolved oxygen, and nutrient salts were measured at different retention times (1, 7, 10, 14, 15, and 28 days). For the batch experiment, an increase in pH, true color, oxidation-reduction potential, dissolved oxygen, nitrite, nitrate, and sulfate were observed over time. On the other hand, ammonia and phosphate decreased to acceptable levels according to standards. The same trend was observed from the installation, with the addition of the reduction of Silica and increase of calcium ions released by the GCA. It can be concluded from the results we gathered that the Philippine GCA is as effective than Japan GCA in terms of wastewater remediation. Although Philippine GCA reduced ammonia and phosphate levels to acceptable values, other parameters such as nitrate and sulfate have to be further studied as they are also part of the water quality standards.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Coal ash; Sewage -- Purification